2015
DOI: 10.1007/s00253-015-6814-8
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of two 16S rRNA gene-based PCR primer sets provides insight into the diversity distribution patterns of anammox bacteria in different environments

Abstract: Due to the high divergence among 16S rRNA genes of anammox bacteria, different diversity pattern of the community could be resulted from using different primer set. In this study, the efficiencies and specificities of two commonly used sets, Amx368F/Amx820R and Brod541F/Amx820R, were evaluated by exploring the diversity characteristics of anammox bacteria in sediments from marine, estuary, and freshwater wetland. Statistical analysis indicated that the base mispairing rate between bases on 16S rRNA gene sequen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 61 publications
1
6
0
Order By: Relevance
“…Two sets of data were generated for each of the samples, and were then combined into one dataset. Similar to previous findings ( Vahjen et al, 2010 ; Cai et al, 2013 ; Starke et al, 2014 ; Wang et al, 2015 ), the species composition of the microbial communities showed great variations between the two original datasets (Supplementary Figures S1 , S2 ). In addition, the original datasets “Qiagen-338-806” and “MP-515-907” revealed 2,438 and 1,947 OTUs, respectively.…”
Section: Resultssupporting
confidence: 87%
See 2 more Smart Citations
“…Two sets of data were generated for each of the samples, and were then combined into one dataset. Similar to previous findings ( Vahjen et al, 2010 ; Cai et al, 2013 ; Starke et al, 2014 ; Wang et al, 2015 ), the species composition of the microbial communities showed great variations between the two original datasets (Supplementary Figures S1 , S2 ). In addition, the original datasets “Qiagen-338-806” and “MP-515-907” revealed 2,438 and 1,947 OTUs, respectively.…”
Section: Resultssupporting
confidence: 87%
“…It has been widely reported that different DNA extraction methods and primer sets targeting different hypervariable regions of 16s rRNA gene would reveal distinct species compositions of natural microbial communities ( Vahjen et al, 2010 ; Cai et al, 2013 ; Starke et al, 2014 ; Wang et al, 2015 ). In some extreme cases, dominant taxa revealed from one combination of DNA extraction and primer set can become rare taxa or even disappear in another combination ( Cai et al, 2013 ; Starke et al, 2014 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Candidatus Scalindua was almost the only genus found in marine sediments, such as South China Sea ( Hong et al, 2011a ), Bohai Sea ( Dang et al, 2013 ), and Arabian Sea ( Woebken et al, 2008 ). In contrast to marine environments, all of these genera of anammox bacteria have been detected in soil ecosystems ( Wang et al, 2015 ; Yang et al, 2017 ). Zhu et al (2011) found that the 16S rRNA gene sequence of fertilized paddy soil were related to four different genera of anammox bacteria.…”
Section: Introductionmentioning
confidence: 99%
“…systems (Yang et al, 2012;Lipsewers et al, 2016), with a totally different community structure than described in freshwater lakes (Wang et al, 2015). So far, however, very little attention has been paid to the role of anammox processes in saline lakes.…”
mentioning
confidence: 99%